PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA DINAS TATA RUANG DAN CIPTA KARYA - -, Jumi (Jurnal Mahasiswa Prodi SI Manajemen, 2013)
Growth of Human Resource management ( SDM) is in this time pushed by progress of civilization of education, science, and technology. Organizer of this sumberdaya of vital importance to reach the target of organization [pass/through] management is appliance to reach the target. In attainment of institution target many unsure-unsur becoming important matters in accomplishment of him, among others is leadership element or leader. Leadership style a motivation and leader given by leader to the subordinate of very have an effect on to subordinate performance in this case is officer. Performance which either from subordinate can be obtained with leadership style and good leader motivation also. Performance are obtained way from both the things in finishing work or duty a and a[n important matter in the effort institution to reach a[n institution target. This research to know influence of leadership style to performance, leadership style [relation/link] with performance, performance storey;level, officer On duty Planology and Creature Masterpiece, leadership style weared by Leader On duty Creature Masterpiece and planology of Rokan pate;upstream. This research use research of deskripti, population in this research counted 50 people, sampelnys counted 50 people by using technique of samling saturated. Pursuant to research got that leadership style very influence Officer performance, there [is] relation between leadership style to officer performance, officer performance On duty Creature Masterpiece and planology Whether, leadership style weared by leader On duty Planology and Creature Masterpiece are Autoritary Leadership style.